The Role of Traditional Market Retribution Subsectors on Local Own Revenue in Ternate City - Mohammad Kotib (AIBPM Publisher, 2020)
Ternate city has several modern and traditional markets. This study focuses on the traditional markets. They are found in several locations, such as in Gamalama village, Dufa-Dufa village, and Bastiong village. Meanwhile the local government builds traditional markets in Kota Baru village. The existence of traditional markets as centers for trade contribute to the Local Own-source Revenue of the region from retributions. Ternate's Own-source Revenue increased during the period of 2010 to 2015, as well as the level of retribution as one of its contributing factor. This study aims to determine the development of traditional market retribution and their perks sector of the Local Own-source Revenue of Ternate City. This study was carried out in Ternate City. This study is a descriptive research with secondary data analysis. The data were analyzed with simple linear regression tools in time series formatted as Y = β + x. The study findings reveal that there is a very strong relationship between Local Own-source Revenue and traditional market retribution. The correlation coefficient (R) of 0.987 and the coefficient of determination (R2) of 0.975 illustrate 97.5% contribution to the revenue. It recommends the Ternate Local Government to perfectly manage the retribution to realize a positive relationship between the fees taken and the service provided. This is mutually beneficial between the government and the community in general.